2013
DOI: 10.1080/00140139.2013.835074
|View full text |Cite
|
Sign up to set email alerts
|

A kinematic analysis of directional effects on mouse control

Abstract: The directional effects associated with cursor movement controlled by a computer mouse have long been studied to improve mouse performance during precise tasks. However, those studies have rarely considered the kinematic variables associated with directional effects and have only analysed the projection of trajectories along the main axes of movement, eventually reducing the original dimensions of the data. In addition, as the angle of approach has a limited number of levels, it has been difficult to observe s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Although horizontal movement is a special case for mouse movement [14], it is the most commonly used tracking axis in FPS games since players often make side-to-side evasive movements along a ground plane. The only factor within a lag condition is target speed.…”
Section: Target Trackingmentioning
confidence: 99%
“…Although horizontal movement is a special case for mouse movement [14], it is the most commonly used tracking axis in FPS games since players often make side-to-side evasive movements along a ground plane. The only factor within a lag condition is target speed.…”
Section: Target Trackingmentioning
confidence: 99%
“…First, distributions of M T for pointing actions are notoriously skewed right, so we will follow previous recommendations [28] and use the geometric mean to estimate a central tendency. Second, target acquisition time is affected by typical Fitts study parameters such as distance (D) and target size (W), but also direction (DI R) [16], possibly differently for each participant (P). We therefore need to estimate M M T separately for different conditions:…”
Section: Adapting Existing Methodologymentioning
confidence: 99%
“…2-a) with a majority (9) answering "Once every 2-3 days or less". A majority of partici pants (16) reported that it felt "Very-" or "Extremely annoying" overall ( Fig. 2-b), and no-one answered "Not annoying at all."…”
Section: Overall Impressionsmentioning
confidence: 99%
“…Despite the publication of a research paper specifically dedicated to highlighting this issue in 2011 [7], reporting these elements systematically in experiment descriptions is still not standard (see e.g. [1,10,19,21,23,25,31]) which can make their replication impossible. Fortunately, several projects provide enough details about the input and output devices' resolution, operating system, and mouse configuration settings to allow exact replication of a transfer function [9,28,30,34,39,41].…”
Section: The Importance Of Accurately Reporting Pointing Conditionsmentioning
confidence: 99%
“…The task was similar to Study 1, except that the circular targets were presented in a 1D reciprocal pattern (left-right) rather than in a circular pattern. We chose a 1D task to reduce any source of variance related to the direction of movement [21] and increase the likelihood of observing significant differences between the functions, which would contradict our assumption that the functions perform similarly.…”
Section: Taskmentioning
confidence: 99%